GENOTYPING OF TOXOPLASMA GONDII IN CEREBRAL AND OCULAR TOXOPLASMOSIS - Mayashinta, Dearikha Karina; Halleyantoro, Ryan; Sari, Ika Puspa; Kurniawan, Agnes (Journal of Tropical Life Science, 2018)
Toxoplasma gondii is an obligate intracellular protozoon, spread world-wide and capable of infecting birds and mammals. Genetic information on T. gondii type that causes human toxoplasmosis is limited. In this study, genetic analysis of SAG2 locus was used to determine the genotype of T. gondii from cases with cerebral and ocular toxoplasmosis in Indonesia. Genotype determination was done directly on the clinical samples. A number of 28 cerebrospinal fluid and 8 vitreous humor positively infected with T. gondii, underwent PCR-RFLP to classify each isolate into one of three genotypes of T. gondii. Type I was the most common found suggesting that cerebral and ocular toxoplasmosis in Indonesia is mostly caused by type I strain of T. gondii.